Inhibition of p38MAPK signalling prevents epidermal blistering and alterations of desmosome structure induced by pemphigus autoantibodies in human epidermis. (1st December 2017) - Egu, D.T.; Walter, E.; Spindler, V.; Waschke, J.
Summary: Background Pemphigus vulgaris (PV) is a skin blistering disease caused by autoantibodies targeting the desmosomal adhesion proteins desmoglein (Dsg) 3 and 1. The mechanisms underlying pemphigus skin blistering are not fully elucidated but p38 mitogen‐activated protein kinase (p38MAPK) activation is one of the signalling events necessary for full loss of cell cohesion. However, it is unclear whether ultrastructural hallmarks of desmosome morphology as observed in patients' lesions are mediated by p38MAPK signalling. Objectives In this study, we tested the relevance of p38MAPK for blister formation and the ultrastructural changes induced by PV autoantibodies in human skin. Methods Human skin samples were injected with IgG fractions of one patient suffering from mucocutaneous PV (mcPV‐IgG), one from mucosal‐dominant PV (mdPV‐IgG) or AK23, a pathogenic monoclonal Dsg3 antibody derived from a pemphigus mouse model. Samples were processed for histological and electron microscopy analyses. Results mcPV‐IgG and AK23 but not mdPV‐IgG reduced desmosome size, caused interdesmosomal widening and formation of split desmosomes, and altered keratin filament insertion. In contrast, full epidermal blister formation and lower desmosome number were evident in tissue samples exposed to mcPV‐IgG only. Pharmacological inhibition of p38MAPK blunted the reduction of desmosome number and size, ameliorated interdesmosomal widening and loss of keratin insertion and prevented mcPV‐IgG‐induced blister formation. Conclusions Our data demonstrate that blistering can be prevented by inhibition of p38MAPK in the human epidermis. Moreover, typical morphological alterations induced by mcPV‐IgG such as interdesmosomal widening and the reduction of desmosome size at least in part require p38MAPK signalling.